2009
DOI: 10.1177/1084713809348372
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Midbrain Implant: A Review

Abstract: The auditory midbrain implant (AMI) is a new hearing prosthesis designed for stimulation of the inferior colliculus in deaf patients who cannot sufficiently benefit from cochlear implants. The authors have begun clinical trials in which five patients have been implanted with a single shank AMI array (20 electrodes). The goal of this review is to summarize the development and research that has led to the translation of the AMI from a concept into the first patients. This study presents the rationale and design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 134 publications
1
48
0
Order By: Relevance
“…[12][13][14] In previous experiments, a reduced fibroblast growth on microstructured platinum surfaces was demonstrated. 15 Further optimization of the electrode-neuron interface could be achieved by directing the orientation of neurons, especially in central auditory prosthesis with close contact to the neurons, such as AMI 16,17 and ABI. 18 Parallel microgrooves on surfaces of various materials had been shown to promote the alignment of neuronal cells, [19][20][21][22][23][24][25] astrocytes, 26,27 as well as fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] In previous experiments, a reduced fibroblast growth on microstructured platinum surfaces was demonstrated. 15 Further optimization of the electrode-neuron interface could be achieved by directing the orientation of neurons, especially in central auditory prosthesis with close contact to the neurons, such as AMI 16,17 and ABI. 18 Parallel microgrooves on surfaces of various materials had been shown to promote the alignment of neuronal cells, [19][20][21][22][23][24][25] astrocytes, 26,27 as well as fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Although historically NF2 patients have had exceedingly limited benefit from ABIs due to the detrimental nature of the tumors, more recent studies from Europe have reported considerable success in ABI performance in NF2 patients, including a mean open-set speech perception of 41% at 24 months post-ABI activation in 18 NF2 patients [77]. Notably, a penetrating ABI and an auditory midbrain implant inserted into the inferior colliculus did not lead to an increased benefit over the ABI [69,70,138].…”
Section: Auditory Nucleus and Ganglion Stimulationmentioning
confidence: 93%
“…Worldwide, more than 100,000 people with hearing loss use cochlear implants to compensate for their impairments, and they can even hear and understand speech. 135 Similarly, retinal stimulation can elicit visual percepts in patients with vision loss. 136,137 Ongoing development of electrodes and stimulation parameters has provided basic letter recognition, orientation, and improved visual acuity in blind patients.…”
Section: Current Interfaces In the Cnsmentioning
confidence: 99%